Accounting Information System Design in iFrames : Case Study on Health Sector Blud of Jakarta Province - Bramadhani Tribuana (AFEBI Accounting Review, 2019)
This research was conducted based on the absence of an adequate accounting information system (AIS) that can be applied to the Regional Public Service Agency (BLUD) on Jakarta Provincial Government and integrated with budget planning, asset, and inventory information system. This fact is supported by the Indonesian Supreme Audit Institution (BPK) report (2016) that states the existing AIS does not provide complete reporting features, and as a consequence, the stages of preparing financial statements are still done manually.This research is expected to help identify information system needs, as well as provide logical model designs of AIS as a part of Integrated Financial Reporting and Management Information System (iFRAMES) that are graphically described in data flow diagrams.This research use case study with data triangulation approach, including interviews and document review. Contingency Theory and PIECES Framework are used in analyzing organizational needs for AIS and using the Framework for the Application of System Thinking (FAST) developed by Whitten and Bentley (2007) as a basis for systems development method theory. This study found that the absence of an adequate AIS has the potential to cause various things, including incomplete accounting cycle, increasing the risk of error in recording and classifying account.